Effect of giving banana hearts on breast milk production in postpartum mothers - Us, Hafsah; Safitri, Mey Elisa; Br Sembiring, Julina (Institute of Computer Science (IOCS), 2024)
One way to create a quality next generation is by providing exclusive breastfeeding, because the nutrition that children need, especially from birth to 6 months of age, can be fulfilled by breast milk without additional drinks and other foods. The proportion of babies receiving exclusive breastfeeding up to August 2017 was around 40%, which has increased compared to 2012, around 38%. WHO targets that by 2025, 50% of children under five will receive exclusive breastfeeding, and giving banana blossoms is a form of support for mothers so that breastfeeding coverage can be realized. type of research with post test only. The sample of 32 postpartum mothers in the work area of the Independent Practice of Midwife Syafriani, Nibong Baroh Village, Nibong District, North Aceh Regency, was taken using purposive sampling and analyzed using the Wilcoxon Test. The results of the Wilcoxon test showed that there was a difference in the average value of breast milk production, p value 0.002, which means that giving banana blossoms was effective in increasing breast milk production. The conclusion obtained from this research is that there is a difference in the average effect of giving banana blossoms before and after giving banana blossoms on breast milk production with a p value of 0.002. It is hoped that postpartum mothers can use banana blossoms to increase breast milk production so that the achievement of exclusive breastfeeding increases.